Optimalisasi Kinerja UMKM Tempe Melalui Skill Manajerial Kewirausahaan - Etty Zuliawati Zed; Ropida yulianti; Imelin Sagita S Pardosi; Naila Putri Inayah; Azhar Alhaq Maulna; Amelia Septiani (Lembaga Pengembangan Kinerja Dosen, 2024)
This service aims to improve the knowledge and skills of Tempe small and medium-sized enterprise (SME) entrepreneurs in effectively managing their businesses and enhancing competitiveness. This service activity is carried out through a series of workshops, motivational training, and group mentoring. The community partners involved in this project were the Tempe SMEs located in the Pejuang neighborhood, Bekasi. The results of this service showed a significant improvement in the knowledge and skills of the Tempe SME entrepreneurs after participating in the training and mentoring sessions. They successfully enhanced their business performance, expanded market access through digital marketing, and formed a group or association of Tempe SMEs to share knowledge and support each other in addressing business challenges. This initiative positively contributed to the welfare and local economic growth by strengthening the Tempe sector as a key pillar of the economy in the Pejuang neighborhood